NMR metabolomics reveals metabolic alterations in a novel mouse model of neurodegeneration - Mercer, Grace V.; Adams, Haley; Locke, Drew P.; Kiefte, Sophie; Harvey, Nikita; Coffey, Rachel; Schneider, Céline M.; Cahill, Lindsay S. (Frontiers in Neuroscience, 2026)
IntroductionThe relationship between brain metabolism and neurodegenerative diseases is poorly understood. To investigate the pathophysiology of neurodegeneration, we used decrepit (dcr) mice, a mouse model with a mutation in a mitochondrial associated gene (mitochondrial ribosomal protein L3, Mrpl3) that results in reproducible, adult-onset degeneration of the brain.MethodsMetabolite profiles were determined using 1H magic angle spinning nuclear magnetic resonance (600 MHz spectrometer) and ex vivo tissue samples from five brain regions in female and male dcr and healthy control mice (n = 39–44 mice/genotype/sex from 44–145 days of age).ResultsThe relative concentration of acetate, N-acetylaspartate, gamma-aminobutyric acid, glutamine, and asparagine were decreased in the dcr mice compared to controls (p < 0.05). When the data was disaggregated by sex, the male dcr mice showed decreased relative concentrations of acetate, N-acetylaspartate, gamma-aminobutyric acid, asparagine, and choline-containing compounds compared to controls (p < 0.05) while the female dcr mice had an elevated relative glucose concentration compared to controls (p < 0.05).DiscussionThe dcr mice show evidence of significant metabolic dysregulation and add to the existing literature on the metabolic consequences of neurodegeneration. This work motivates future studies to understand the connection between mitochondrial dysfunction, metabolic alterations and neurodegeneration using the dcr mouse model.